An analysis of the practice, knowledge, and perception of Valencian Pelota in Valencian society - Sanahuja-Peris, Guillermo; Agulló-Calatayud, Víctor (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
In the Comunitat Valenciana an autochthonous modality called "Valencian Pelota" is played, which nowadays tries to compete in terms of players and audience with the major global sports. This study aimed to find out the current situation of this sport in terms of practice, knowledge and perception by Valencian society. The methodology consisted of a combination of quantitative and qualitative techniques. A total of 1,468 surveys were carried out across three study universes. In addition, 4 focus groups and 33 in-depth interviews with representatives of interest groups served to contrast the data obtained and to discuss, in a dialogical process, the situation and challenges of this sport. The most important findings of this study showed that " Valencian Pelota" maintains an acceptable level of practice within its own territory: 14.6% of Valencians have played it at least once, with 28.8% of those under 35 standing out, clearly reflecting the impact of the educational program "Pilota a l’escola." Awareness is also relatively positive, with 21.6% of the general population having a medium level of knowledge and 7.1% having a high or very high level of knowledge. These figures, compared with other studies on the level of practice and sports participation, show that pelota in the Valencian Community is positioned somewhere between minority sports and mainstream sports.